Surgical Treatment of Dynamic Nasal Collapse - Ji, Keven Seung Yong; Krane, Natalie A. (Facial Plastic Surgery, 2022)
Nasal obstruction is a prevalent issue that significantly impacts patient quality of life and contributes to a large-scale financial burden. Internal or external nasal valve collapse may play a role in nasal obstruction, with varying etiologies. Surgical correction of nasal valve collapse is indicated when septal and/or turbinate surgery alone are not sufficient in correcting the nasal obstruction. The choice of how to address nasal valve repair depends on presenting findings, associated aesthetic concerns, particularly of the nasal tip, patient anatomy, and surgeon preference. This article provides a methodical approach to the diagnosis of nasal valve collapse, indications for repair, and provides detailed explanation of the operative techniques used to address nasal valve collapse, while also discussing the advantages and disadvantages of each approach.
Keywords: nasal obstruction; nasal valve collapse; septorhinoplasty; spreader grafts; lateral crural strut grafts